2015
DOI: 10.3390/catal5042309
|View full text |Cite
|
Sign up to set email alerts
|

Switching off H2O2 Decomposition during TS-1 Catalysed Epoxidation via Post-Synthetic Active Site Modification

Abstract: Despite its widespread use, the Lewis acidic zeolite, TS-1, still exhibits several unfavourable properties, such as excessive H2O2 decomposition, which decrease its overall performance. In this manuscript, we demonstrate that post-synthetic modification of TS-1 with aqueous NH4HF2 leads to modifications in epoxidation catalysis, which both improves the levels of epoxide selectivity obtained, and drastically minimises undesirable H2O2 decomposition. Through in situ spectroscopic study with UV-resonance enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…However, more uniform can also imply more selective to the desired reaction pathway, by minimizing side reactions and/or competitive reactions induced by alternative active sites. A key example of how this can be achieved can be highlighted from some of our team's recent research focused upon catalytic epoxidation with TS-1 [ 91 ]. Therein, we demonstrated that post-synthetic treatment of TS-1 with NH 4 HF 2 and H 2 O 2 , following studies of Balducci et al [ 92 ] resulted in the formation of a catalyst that was equally as active for catalytic epoxidation, but dramatically more efficient with respect to the oxidant, H 2 O 2 .…”
Section: Perspectives and Pertaining Challengesmentioning
confidence: 99%
“…However, more uniform can also imply more selective to the desired reaction pathway, by minimizing side reactions and/or competitive reactions induced by alternative active sites. A key example of how this can be achieved can be highlighted from some of our team's recent research focused upon catalytic epoxidation with TS-1 [ 91 ]. Therein, we demonstrated that post-synthetic treatment of TS-1 with NH 4 HF 2 and H 2 O 2 , following studies of Balducci et al [ 92 ] resulted in the formation of a catalyst that was equally as active for catalytic epoxidation, but dramatically more efficient with respect to the oxidant, H 2 O 2 .…”
Section: Perspectives and Pertaining Challengesmentioning
confidence: 99%
“…In several liquid-phase epoxidation routes to convert propene into propene oxide, much attention has been directed to heterogeneous catalytic oxidation using hydrogen peroxide as a more environmentally benign and profitable chemical process [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. Titanium silicalite (TS-1) catalyst has been extensively investigated for this route because propene oxide can be produced with a high selectivity in methanol under mild conditions [4,5,[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The direct epoxidation process based on hydrogen peroxide (oxidant) and TS-1 (catalyst) was commercialized and referred to as "hydrogen peroxide-to-propene oxide" (HPPO) process.…”
Section: Introductionmentioning
confidence: 99%
“…S1 †), complicated post-treatment processes were still required to improve the catalytic ability of the Ti centers. [40][41][42] The TON of commercial TS-1 could reach 136, which is much higher than the TON (80) of TS-1 directly synthesized using the traditional system. However, post-treatment would leach the Ti species from the TS-1 framework, leading to a lower framework Ti content.…”
Section: Gel Compositionmentioning
confidence: 88%